Quality attributes of fresh poultry meat wrapped in corn starch-based films incorporated with nanocellulose fiber and thymol for active packaging application - Othman, Siti Hajar; Nordin, Norhazirah; Kadir Basha, Roseliza; Abdul Rashid, Suraya (2024)
Abstract: Corn starch (CS)-based films incorporated with nanocellulose fiber (CNF) and thymol (Thy) were prepared via the solution casting method. The combined effect of CNF and Thy on quality attributes of fresh chicken meat stored at 10 °C was investigated regarding visual appearance, weight loss, pH, and total viable count (TVC). In terms of visual appearance upon 7 days of storage, chicken meat samples exhibited shrinkage due to moisture loss, except for the sample wrapped in commercial film. However, the samples wrapped in CS/CNF/Thy films had better visual appearance, odor, and minimal pH change. Microbial populations were the lowest for sample wrapped in CS/CNF/Thy film compared to the CS and commercial films. In brief, the application of the active film considerably delayed the growth of microorganisms on chicken meat sample, increasing the food shelf life (<7 days) compared to control samples (<3 days) thus promising for active food packaging application.